Social Media Promotions and Reviews Drive Online Shopping in Indonesia: Promosi dan Ulasan Media Sosial Mendorong Belanja Online di Indonesia - Sari, Elda Premesta; Indayani, Lilik; Abadiyah, Rifdah (Indonesian Journal of Innovation Studies, 2024)
This study investigates the effects of social media promotions, prices, and product reviews on purchasing decisions for online shopping through Shopee in Sidoarjo. Using a quantitative approach, data from 96 respondents was collected via a Google Forms questionnaire. Analysis through SPSS version 26 revealed that social media promotions and product reviews significantly influence purchasing decisions, while price does not. These findings suggest that Shopee should focus on enhancing social media promotions and product reviews to boost consumer interest. Future research should explore additional factors to provide a more comprehensive understanding of online purchasing decisions. Highlight: Social media promotions significantly influence purchasing decisions on Shopee. Product reviews have a notable impact on consumer buying choices. Price does not significantly affect purchasing decisions for Shopee users. Keywoard: Social media promotions, Product reviews, Online shopping, Purchasing decisions, Shopee